A Proposal for Considering Research Integrity from the Perspective of Behavioral Economics - Melissa S. Anderson (American Society for Microbiology, 2014)
This paper proposes that theory and findings from behavioral economics may shed light on research integrity and misconduct. It suggests ways in which strategies based on behavioral theory and research might be used by principal investigators to support research integrity among their research teams.